Export Performance of Indonesian Processed Tuna Commodities in the Japanese Market - Kristiani, Mikha; Suharno, Suharno; Harmini, Harmini (Agro Bali : Agricultural Journal, 2023)
Tuna commodity is globally competitive, but its performance is still below its competitor country, namely Thailand and is starting to compete with other countries, namely the Philippines, Vietnam and China. This study aims to evaluate the competitiveness performance and analyze the demand for processed tuna commodities in the Japanese market. Export competitiveness analysis is processed using the Revealed Comparative Advantage (RCA) index and the Revealed Competitiveness Advantage (RC) index. The level of competition and export demand will be analyzed using the Almost Ideal Demand System (AIDS) model. The results showed that the export performance of Indonesian processed tuna commodities was comparatively and competitively competitive in the Japanese market. The demand for Indonesian processed tuna commodities in the Japanese market has fulfilled the demand theory. Indonesian processed tuna is a normal item for Japanese consumers. For Indonesia, processed tuna from competitor countries Thailand, the Philippines, Vietnam, and China are substitute goods. Thus, an increase in prices in these four countries will increase Indonesia's share.